Evaluation features of intellectual capital at the micro and macro levels. - Golovash, B.; Golovash, L. (Ways to Improve Construction Efficiency, 2019)
The article analyzes the features of approaches to the assessment of the intellectual capital of enterprises. A comparative analysis is made of existing methods for evaluating intellectual capital and possible options for their use. The importance of innovation in determining the intellectual potential of individual enterprises and the country as a whole is determined. It is researched an innovative rating of the countries of the world and the place of Ukraine in it.